2004
DOI: 10.1159/000074669
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Reserpine-Induced Orofacial Dyskinesia and Cognitive Dysfunction by Quercetin

Abstract: Tardive dyskinesia (TD) is a serious neurological syndrome associated with long-term administration of neuroleptics to humans and experimental animals. The pathophysiology of this disabling and commonly irreversible movement disorder is still obscure. It may be caused by a loss of dopaminergic cells or may be due to free radicals as a product of high synaptic dopamine levels. Quercetin is a bioflavonoid with strong antioxidant properties. Repeated treatment with reserpine (1.0 mg/kg) on each other day for a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…In this sense, the chronic quercetin treatment for 30 days in doses of 10, 25 and 50 mg/kg, reverses cognitive deficits in aged and ethanol-intoxicated mice . Quercetin in doses of 50 and 100 mg/kg significantly and dose-dependently reduced the reserpine-induced vacuous chewing movements and tongue protrusions in rats (Naidu et al, 2004). Besides, this flavonoid in doses of 25-100 mg/kg proved to be a useful agent in neuroleptic-induced orofacial dyskinesia .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this sense, the chronic quercetin treatment for 30 days in doses of 10, 25 and 50 mg/kg, reverses cognitive deficits in aged and ethanol-intoxicated mice . Quercetin in doses of 50 and 100 mg/kg significantly and dose-dependently reduced the reserpine-induced vacuous chewing movements and tongue protrusions in rats (Naidu et al, 2004). Besides, this flavonoid in doses of 25-100 mg/kg proved to be a useful agent in neuroleptic-induced orofacial dyskinesia .…”
Section: Discussionmentioning
confidence: 83%
“…Reports on the neuroprotective effects of quercetin have also utilized chronic administration for some weeks and by an oral route. Hence, quercetin treatment for 30 days reverses cognitive deficits in aged and ethanol-intoxicated mice , and quercetin for a period of 4 weeks significantly and dose-dependently reduced reserpineinduced vacuous chewing movements and tongue protrusions in reserpine-treated animals (Naidu et al, 2004). After 21 days quercetin also proved to be a useful therapeutic agent in neuroleptic-induced orofacial dyskinesia .…”
Section: Introductionmentioning
confidence: 84%
“…Dopamine VMAT blockade by reserpine promotes dopamine oxidative catabolism by MAO (9). As a result, dopamine-quinones and hydrogen peroxide are formed leading to oxidative stress (4,17) in areas of the brain rich in monoamines such as the basal ganglia which are more vulnerable to free radical damage (15). The neuronal damage of the basal ganglia is associated with damage of voluntary movements (7).…”
Section: Discussionmentioning
confidence: 99%
“…The neuro-protective effects of plants containing polyphenolic compounds such as quercetin [43] and anthocyanins [44] have been previously reported. Moreover, it has been demonstrated that polyphenolic compounds have Ache inhibitory activity and antioxidant effect on brain [38, 45, 46].…”
Section: Discussionmentioning
confidence: 99%